Champa chahti jamat k lia urdu ka guldasta - Ahsaan,Fouzia Farooqi (Karachi: Oxford university press, 2024)
The Oxford Champa Class 6 book is part of the Oxford University Press series used in Pakistan to meet the educational requirements of middle school students. The book is designed to align with Pakistan$1 (Bs national curriculum, offering a blend of subjects to foster comprehensive academic and personal development. In this book, students engage with classic and contemporary Urdu literature, including prose, poetry, and essays. It aims to enhance reading comprehension, grammar, and writing skills while introducing students to significant cultural, social, and moral themes.s
Keywords: Champa- textbook